Commensal Microbiome Expands Tγδ17 Cells in the Lung and Promotes Particulate Matter-Induced Acute Neutrophilia - Yang, Chorong; Kwon, Dong-il; Kim, Mingyu; Im, Sin-Hyeog; Lee, You Jeong (Frontiers in Immunology, 2021)
Particulate matter (PM) induces neutrophilic inflammation and deteriorates the prognosis of diseases such as cardiovascular diseases, cancers, and infections, including COVID-19. Here, we addressed the role of γδ T cells and intestinal microbiome in PM-induced acute neutrophilia. γδ T cells are a heterogeneous population composed of Tγδ1, Tγδ2, Tγδ17, and naïve γδ T cells (TγδN) and commensal bacteria promotes local expansion of Tγδ17 cells, particularly in the lung and gut without affecting their Vγ repertoire. Tγδ17 cells are more tissue resident than Tγδ1 cells, while TγδN cells are circulating cells. IL-1R expression in Tγδ17 cells is highest in the lung and they outnumber all the other type 17 cells such as Th17, ILC3, NKT17, and MAIT17 cells. Upon PM exposure, IL-1β-secreting neutrophils and IL-17-producing Tγδ17 cells attract each other around the airways. Accordingly, PM-induced neutrophilia was significantly relieved in γδ T- or IL-17-deficient and germ-free mice. Collectively, these findings show that the commensal microbiome promotes PM-induced neutrophilia in the lung via Tγδ17 cells.